2019
DOI: 10.3390/pr7100766
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Stability Condition Derivation for Position Closed-Loop System in Hydraulic Automatic Gauge Control

Abstract: In the metallurgical industry, hydraulic automatic gauge control (HAGC) is a core mechanism for thickness control of plates used in the rolling process. The stability of the HAGC system’s kernel position closed-loop is key to ensuring a process with high precision, speed and reliability. However, the closed-loop position control system is typically nonlinear, and its stability is affected by several factors, making it difficult to analyze instability in the system. This paper describes in detail the functionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
Section: Literature Overviewmentioning
confidence: 99%
“…In terms of roughness, the total pressure loss value was reduced by 23.1% compared to the smooth blade. Han et al [26] used numerical methods to study the influence of blade surface roughness on the internal flow field and characteristic parameters of the compressor under the compressor-level environment and found that the blade roughness had a significant effect on the main performance parameters of the compressor; with the blade roughness with the increase of the compressor, the performance degradation of the compressor stage was intensified, and the energy loss of the internal airflow was increased, especially the energy loss of the airflow near the middle and upper part of the leading edge of the impeller was severe, and the temperature of the blade end wall was increased.With the rapid development of computer technology, numerical simulation is increasingly widely used in the fluid flow [27][28][29][30][31][32][33]. Guelich et al [34] studied the effect of wall roughness on the efficiency Energies 2020, 13, 464 3 of 20 of centrifugal pumps.…”
mentioning
confidence: 99%
“…The traditional fault diagnosis method of hydraulic systems mainly relies on the rich working experience of maintenance personnel [8]. The identification accuracy of hydraulic systems is low by means of sensory diagnosis, oil sample analysis, and fault tree analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous decades with the rapid development of computer technology, CFD technology has been widely used in many fields, such as pressure fluctuation and vibration [25][26][27], heat and mass transfer [28,29], flow control [30,31]. At the same time, the test method is still one of the effective research methods [32][33][34].…”
Section: Introductionmentioning
confidence: 99%